The Urgency Of Zakat In Sharia Economic Law: A Philosophical Review - Apriansyah, Apriansyah; Waskito, Tejo; Suhardini, Indah (Universitas Islam Negeri Raden Intan Lampung, 2023)
Zakat is the third pillar of Islam which contains the divine dimension (dimensi illahiyah) as well as the human dimension (dimensi insaniyah). The divine dimension refers to the vertical relationship between the servant and God where zakat is an order from Allah that must be fulfilled by every servant. Meanwhile, the human dimension emanates from the horizontal relationship between human beings within which zakat has wide social implications to bridge inequality, injustice and poverty. This study aims to further comprehend the philosophical basis of zakat in part of sharia economic law. This study is a library research that uses a theoretical approach by utilizing relevant literature sources. Thus, this study aims to show that philosophy is the basic foundation for determining the orientation and direction of an economic system based on Islamic sharia principles. This study also concludes that the philosophical aspects of zakat are manifested in the functionalization of zakat which, in addition to being a means of purifying the soul and property from kufr and miserliness, can also be a means to foster a sense of sympathy and social sensitivity among human beings. Keywords: Zakat, Philosophical Foundation, Sharia Economic Law